GAYA KOMUNIKASI DALAM BINGKAI KEPEMIMPINAN BAGI FIGUR PEREMPUAN - Indriani, Sri Seti; Prasanti, Dhita (Universitas Merdeka Malang, 2018)
Good leadership requires competence in communicating with members, how to communicate the leadership of an organization or institution to achieve its goals. In this modern society, more and more women become leaders in their organization which in some parts of society in Indonesia, It is still rare to find women responsible. This study aims to find out more about responsible women in an institution / organization that focuses on how they communicate with their members to achieve goals, so that the title that emerges in this research is